New surgical approach for intrascleral fixation using an intraocular lens with hook‐shaped haptics. Issue 2 (February 2018) - Yoshida, Norihiko; Kojima, Takashi; Yokoyama, Sho; Horai, Rie; Ichikawa, Kazuo
Abstract : N/A: We report a new surgical technique of intrascleral posterior chamber intraocular lens (PC IOL) fixation using a newly developed hook‐shaped haptic IOL (NX‐70CH) and a 25‐gauge loop‐shaped haptic manipulator. Previous techniques of intrascleral PC IOL fixation had 2 major technical challenges; that is, externalization of the haptic and fixation of the haptic into the scleral tunnel. The new IOL and manipulator can facilitate externalization and secure fixation of the IOL haptic and can be used for suture fixation or implantation in the capsular bag in cases with presumed subluxated lens.